A Systematic Review of Validation Practices for the Goal Attainment Scaling Measure. (April 2020) - Shankar, Sneha; Marshall, Sheila K.; Zumbo, Bruno D.
Goal attainment scaling (GAS) is an internationally recognized measure that is widely used in educational, counseling, and clinical settings to identify and evaluate relevant goals for an individual. The GAS is an unusual measure because its content, which consists of goals, is formed by the respondent and/or users in the process of completing the GAS. Using the unified view of validity as a guiding framework, this systematic review examines validation practices and how goals are represented in this measure. This review demonstrates that validation practices tend to focus on aspects that do not support the overall construct validity of the measure, as well as reference to the GAS measure or GAS scores as a property. Several gaps in validity evidence and the various ways goals are conceptualized are described and discussed. The varying ways goals are considered suggest clarity is needed to enhance explanations and score meaning. This review urges researchers to consider ways validity and validation evidence can help verify the many claims that are made about this measure. Future validity research needs to consider application of a theoretical framework and response processes as key aspects of substantiating the construct measured by the GAS.